This book is not rubbish - Thomas, Isabel (London: Wren & Rook, 2018)
Our planet is in peril and it needs your help! But the good news is that there are loads of easy ways that you can make a difference! From throwing a planet party and ditching straws, to banning glitter and becoming an art-activist, helping to save the planet is not as difficult as you think. Covering issues like plastics, pollution, global warming and endangered animals, this is a one-stop guide to becoming an eco-warrior, not an eco-worrier. Discover how to ditch the plastic, reduce your rubbish and start making everyday steps that will make all the difference. It's time to take control of your future and help clear the world of all this rubbish!